Analisis Beban Kerja Petugas Rekam Medis Berdasarkan Metode Workload Indicator Staff Need (WISN) Di Puskesmas Dempo Palembang Tahun 2021 - Maisarah, Fitri (JOURNAL OF HEALTH SCIENCE, 2024)
One method of calculating the workload according to PERMENKES No. 33 of 2015 concerning Guidelines for the Preparation of Human Resource Needs Planning is to use the WISN method. The Staff Needs Indicator (WISN) workload method is a method of calculating the need for Health Human Resources. The purpose of this study was to calculate the available working time and the standard of slack for medical officers at the Dempo Palembang Health Center. The research method uses descriptive quantitative. Data collection techniques in this study using interviews, observation and documentation. The research instrument used writing instruments, notebooks, cameras and stopwatches. The data analysis technique used the Workload Indicator Staff Need (WISN) method. Based on research on working days at the Dempo Palembang Health Center as many as 1911 hours/year or 114,600 minutes/year, the main activities in the medical record room include searching for medical record files and returning medical record files to the storage rack, the standard workload is 318,500 minutes, the standard allowance is 0 .09 minutes and the number of staff needed for opening 1 person. Suggestion for Dempo Palembang health center to add 1 more person. Keywords : Officer, Method, Workload